2004
DOI: 10.1111/j.1349-7006.2004.tb03234.x
|View full text |Cite
|
Sign up to set email alerts
|

Thymus‐leukemia antigen (TL) as a major histocompatibility complex (MHC) class Ib molecule and tumor‐specific antigen

Abstract: Mouse thymus-leukemia antigens (TL) belong to the family of major histocompatibility complex (MHC) class Ib antigens and have a unique mode of expression, i.e., in contrast to other MHC class Ib or Ia antigens, they are found restricted to the intestines in all mouse strains, but also in the thymus of certain strains (TL + strains). Nevertheless, a proportion of T lymphomas/leukemias in strains that do not express TL in the thymus (TL -strains) feature TL as a tumor antigen. TL was originally defined serologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Commercially available systems (http://www.siliconbiosystems.com) have extended these limits to 40,000 independently routable cages. To improve throughput to an extent that would make the assay useful to test nonclonal target and effector cells obtained from live organisms, the preliminary enrichment of CTL and NK cell populations may be required, by either Ab or tetramer staining (38,39), followed by sorting (40). This exemplifies the complementary nature of DEPArray and classical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Commercially available systems (http://www.siliconbiosystems.com) have extended these limits to 40,000 independently routable cages. To improve throughput to an extent that would make the assay useful to test nonclonal target and effector cells obtained from live organisms, the preliminary enrichment of CTL and NK cell populations may be required, by either Ab or tetramer staining (38,39), followed by sorting (40). This exemplifies the complementary nature of DEPArray and classical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] In addition, their possible roles in situ have been elucidated to a certain extent, [7][8][9] though many issues remain to be clarified. Although TL − strains (e.g., C57BL/6 (B6) and C3H/He (C3H)) do not express TL in the thymus, a proportion of T lymphomas originating in these mice express TL as a serologically defined tumor antigen.…”
mentioning
confidence: 99%
“…[1][2][3][4] Recent studies by us and others showed that TL molecules bind with CD8αα + intestinal intraepithelial lymphocytes, CD8 + thymocytes and CD8αα + peripheral T lymphocytes. [5][6][7][8] In addition, their possible roles in situ have been elucidated to a certain extent, [7][8][9] though many issues remain to be clarified. Although TL − strains (e.g., C57BL/6 (B6) and C3H/He (C3H)) do not express TL in the thymus, a proportion of T lymphomas originating in these mice express TL as a serologically defined tumor antigen.…”
mentioning
confidence: 99%